Antimicrobial peptides as promising additives to Awassi lambs nutrition - A. M. M. Mani (Bulgarian Journal of Veterinary Medicine, 2025)
Due to restrictions on the use of antibiotics in livestock, novel feed additives are urgently needed to improve feed efficiency and simultaneously reduce disease. This study investigated whether the addi-tion of antimicrobial peptides (AMPs) to the diet affects the production traits, enzymes, and epithe-lium of rumen in Awassi lambs. Twenty-four 2–2.5-month-old Awassi lambs weighing 15.8±1.2 kg were randomly divided into four groups: control (fed basal diet), D-AMPs (20 mg/kg defense peptide as a basal diet supplement), Lf-AMPs (20 mg/kg lactoferrin peptide as a basal diet supplement), Mix-AMPs (10 mg/kg defense and lactoferrin peptides as a basal diet supplement). The results revealed that dietary supplementation with AMPs improved performance namely final body weight (FBW), total weight gain (TWG), average daily gain (ADG), and feed conversion efficiency (FCR), but no effect was observed on dry matter intake. The parameters of the rumen fluid were measured at 0, 45, and 90 days of the experiment. According to the results, the sampling days did not affect the ruminal pH (P ≥ 0.05). The concentrations of NH3 and total volatile fatty acids (TVFA) increased in the Mix-AMPs group on the 90th day of the experiment, while the concentration of acetate was highly in-creased (P≤0.05) on the 45th day compared to the other groups. The concentrations of propionate and butyrate recorded higher values on day 90 in D-AMPs and Mix-AMPs groups. The results showed that AMPs could improve the activities of cellulase, xylanase, lipase, amylase and protease enzymes and ruminal papillae (diameter and micropapillary density). In conclusion, AMPs have proven to be promising additives to replace antibiotics in lamb feed.